1998
DOI: 10.1042/bj3320755
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of soluble penicillin-binding protein 2a of methicillin-resistant Staphylococcus aureus with β-lactams and acyclic substrates: kinetics in homogeneous solution

Abstract: The kinetics of reaction of solubilized penicillin-binding protein 2a (sPBP2a) of methicillin-resistant Staphylococcus aureus with a variety of beta-lactams and acyclic species was studied in homogeneous aqueous solution at 37 degreesC in 25 mM Hepes buffer, pH7.0, containing 1 M NaCl. Under these conditions, but not at lower salt concentrations, protein precipitation did not occur either during or after the reaction. The reactions of beta-lactams in general could be monitored by competition with a chromophori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 33 publications
4
57
0
Order By: Relevance
“…Additionally, we were not able to detect any deacylation of the CPT or ME acyl-enzyme species, while monitoring for four days. Previously it was reported that upon acylation by antibiotics PBP 2a precipitates, 13 or alternatively an oligomerization of the acylated protein could explain the sheltering of the acyl-enzyme species to impart longevity. Neither of these two possibilities is applicable in the cases of CPT or ME binding to PBP 2a, as detailed in Supporting Information.…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we were not able to detect any deacylation of the CPT or ME acyl-enzyme species, while monitoring for four days. Previously it was reported that upon acylation by antibiotics PBP 2a precipitates, 13 or alternatively an oligomerization of the acylated protein could explain the sheltering of the acyl-enzyme species to impart longevity. Neither of these two possibilities is applicable in the cases of CPT or ME binding to PBP 2a, as detailed in Supporting Information.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…In some instances, the E-I complex undergoes deacylation, but the rate of such deacylation is sufficiently slow that the bacterium is deprived of the enzyme function and dies. 7,13 (1)…”
mentioning
confidence: 99%
“…Nitrocefin (120 M) was used as the reporter molecule to determine the apparent first-order rate constants for acylation by other nonchromogenic (or poorly chromogenic) ␤-lactams at varying concentrations in competition experiments (18).…”
Section: Determination Of the Kinetic Parameters For Interactions Of mentioning
confidence: 99%
“…These studies provide the first quantitative measurement of the noncovalent interaction energies of a PBP with covalently bound ␤-lactam antibiotics. Intriguingly, these noncovalent interaction energies do not correlate with the second-order rate constants for formation of the acyl-enzyme complex (k 2 /KЈ), which are considered the best indicators of the inhibitory potency of ␤-lactam antibiotics with PBPs (Frere et al 1975;Frere et al 1992;Jamin et al 1993;Graves-Woodward and Pratt 1998;Lu et al 1999).…”
mentioning
confidence: 99%